A rare case of VACTERL association with a genito-urinary anomaly - Ali, Syed A.; Fahad, M.; Lakshmi, C. V. S.; Mirza, Numeera A.; Sara, Zeba R. (International Journal of Contemporary Pediatrics, 2022)
VACTERL association is a cipher used to describe a cluster of conditions wherein there is a seemingly unexplainable non-random association of specific birth defects of multiple organ systems. It includes vertebral anomalies (V), anal anomalies (A), cardiac anomalies (C), tracheoesophageal fistula (TEF), renal anomalies (R) or radial bone anomalies (R), and limb defects (L). At least three of these seven malformations need to be present to constitute the VACTERL association. Other congenital anomalies of different systems may additionally be present with this association but are classified separately and the rarity of this occurrence is greater than even the VACTERL association. We report a neonate with congenital abnormalities of the cardiac system atrial septal defect and ventricular septal defect, tracheoesophageal fistula H type, and a multicystic dysplastic kidney. Additionally, the baby was also found to have a micropenis, a genito-urinary anomaly. With optimal surgical correction in the post-natal period and vigilant periodic follow-up, the prognosis may be relatively positive. Medical management can be used as therapy for treating long-term sequelae of the anomalies if any. Therefore, morbidity and mortality can be prevented to a great extent with early diagnosis and immediate intervention.